MORPHOLOGICAL ASPECTS OF ESOPHAGEAL ATRESIA WITH DISTAL FISTULA IN NEWBORNS - Makhzuna Kh. Mukhsinova; Erkin A. Eshbaev; Aziz A. Zufarov (Central Asian Journal of Medicine, 2025)
Esophageal atresia is a pathological condition that manifests itself in children by the absence of any connection between the upper and lower segments of the esophagus. This anomaly is one of the relatively common developmental anomalies (in 1 case per 3,500 births). There are 5 different variants of esophageal atresia, which are the most common in terms of clinical morphology and anatomy. Atresia of the esophagus with distal attachment, that is, morphological changes in the 1st variant of this anomaly are not covered at all, the lack of morphological criteria shows that there is a high need for sound fundamental knowledge to propose a solution to the problem.